The Emergence of Fintech on Cost Management in Malaysian Financial Institutions - Nik Abdullah, Nik Herda; Wei Ling, Tye (Indonesian Journal of Economics, Social, and Humanities, 2023)
A good cost management system is vital in ensuring that the final product or service costs do not reflect a large variance from budgeted financial targets. Over time, new information and technologies may be introduced that completely change the production method, business process, or product itself. The term "FinTech" has gained significant attention as a result of various influential factors, such as advancements in technology, the anticipation of business innovation within the market, the need for cost reduction, and the evolving demands of customers. The advent of new digital technologies has led to the automation of various financial activities, potentially offering more efficient and economically viable products across different segments of the financial industry. These segments include lending, asset management, portfolio advice, and the payment system. The main objective of this paper is to provide a synthesis of the impacts of fintech on cost management, which will improve firm value among financial institutions, and to propose a framework for fintech and cost management. It has been found that fintech provides the management with relevant, accurate, and reliable information on the firm’s critical success factors within and outside an organization related to cost management for long-term periods.